(untitled) (Research Papers, 2022)
The cultural differences in internationalization are being defined according to the “GLOBE’s” methodology and examined in the Asian context in the internationalization settings of small and medium-sized Asian enterprises >enterprises. from Japan, China and Malaysia. The purpose is to determine if and what effect the cultural differences exert on the internationalization of these enterprises. On the basis of the theoretical literature review, it can be inferred that the cultural differences appear to be an obstacle for the internationalization of the Asian enterprises. Taken as a whole, the latter emphasizes that the cultural differences in the internationalization of Asian enterprises should not be neglected, and that it is highly recommended that enterprises plan strategies for overcoming cultural differences.